Occupational safety of morticians: A case study of mortuary facilities in Cape Coast, Ghana - Prah, James Kojo; Aggrey, Ebenezer; Kudom, Andreas A.; Abdulai, Mohammed Najimudeen; Banson, Cecil; Addo-Yeboa, Benedict; Pinkrah, Richard; Nkrumah, Kwasi Sobre; Walker, Emmanuel; Atulley, Elizabeth (International Journal of Public Health Science (IJPHS), 2025)
Risk assessment is helpful for risk management because it makes significant workplace concerns easier to understand. Because of the numerous risks involved, the death care sector is regarded as one of the riskiest places to work. Nevertheless, not enough research has been done on the safety of mortuary staff in low-resource environments. This study assessed the risks associated with identified hazards in two mortuary facilities at the University of Cape Coast in Ghana. This was a cross-sectional study that used a combination of methods. Thirty-six morticians participated in the study. Respondents scored low on knowledge, high on attitude, and awareness toward occupational health and safety. Only 9 (25.0%) participants knew the correct concentrations of chlorine solution required to disinfect surfaces. Only two of the six chosen volunteers could reconstitute the chlorine solution for disinfection correctly. Risks of chemical inhalation, musculoskeletal injuries, cuts, and traumatic injuries were evaluated as high. A review of incident registers revealed underreporting of injuries. While the study showed significant gaps in the occupational safety of morticians in low-resource environments, it also presents an opportunity for improvement. Regulatory agencies for morticians in Ghana must set out minimum qualifications for this critical category of health workers.